Licenciamiento de software en las empresas públicas y/o privadas de la ciudad de Tarapoto - Shapiama Rengifo, Rene Grimaldo (2008)
The present thesis presents, explains, demonstrates and shows solutions to the problem of the software license in the public and/or private companies of Tarapoto city; it was determined to work with as public as well private companies through this way to be able to determine in which business or institutional sector exists more deficiencies in relation to the software license installed in its computer parks, for this a field study through surveys to the businesspeople and chief of system of those companies was made, begin able to determine variables that showed the prospective results during the process of data evaluation carried out in the present thesis, likewise demonstrating that in Tarapoto city there is a lot of informality with regard to software licenses. In our country - Peru, the economic impact with regard to the illegality of the software has taken many companies to loss, having to request to institutions in charge of looking after the audit lights to take measures with regard to the tapie through juridical norms that are established in our laws and guided by the Congress of the Republic. Those are the most advance and pioneering laws in Latin America, as regards control, supervision, having the necessity to work as a group for the application of the norms, for example it does not exist a norm that allows to include the moment to present the balances and administration reports, besides having specialized bodies in crime against the intellectual property in the National Police and Public Ministry.